Coordination of Surface‐Induced Reaction and Intercalation: Toward a High‐Performance Carbon Anode for Sodium‐Ion Batteries. Issue 6 (3rd March 2017) - Chen, Weimin; Chen, Chaoji; Xiong, Xiaoqin; Hu, Pei; Hao, Zhangxiang; Huang, Yunhui
Abstract : Oxygen‐rich carbon material is successfully fabricated from a porous carbon and evaluated as anode for sodium‐ion battery. With the strategy of optimal combination of fast surface redox reaction and reversible intercalation, the oxygen‐rich carbon anode exhibits a large reversible capacity (447 mAh g −1 at 0.2 A g −1 ), high rate capability (172 mAh g −1 at 20 A g −1 ), and excellent cycling stability.